Biblical Terror Why Law and Restoration in the Bible Depend Upon Fear - Cataldo, Jeremiah W. (Bloomsbury Academic, 2017)
For biblical authors and readers, law and restoration are central concepts in the Bible, but they were not always so. To trace out the formation of those biblical concepts as elements in defensive strategies, Cataldo uses as conversational starting points theories from Zizek, Foucault and Deleuze, all of whom emphasize relation and difference. This work argues that the more modern assumption that biblical authors wrote their texts presupposing a central importance for those concepts is backwards. On the contrary, law and restoration were made central only through and after the writing of the biblical texts - in particular, those that were concerned with protecting the community from threats to its identity as the "remnant". Modern Bible readers, Cataldo argues, must renegotiate how they understand law and restoration and come to terms with them as concepts that emerged out of more selfish concerns of a community on the margins of imperial political power.